Experimental Study on the Deformation and Permeability Characteristics of Raw Coal under the Coupling Effect of Confining Pressure and Pore Pressure - Kangwu Feng; Kequan Wang; Yushun Yang (Advances in Materials Science and Engineering)
The effects of confining pressure and pore pressure on the deformation and permeability characteristics of raw coal are studied experimentally. The deformation properties of raw coal by fracture and its permeability evolution laws under the coupling effect of confining pressure and pore pressure were further studied using a tri-axial servo-controlled seepage system for thermo-fluid-solid coupling of methane-bearing coal. The effects of confining pressure and gas pressure on the strength, elastic modulus, and permeability of raw coal were also analyzed. From the results, it was observed that rise in the confining pressure results in reduction of the initial permeability of raw coal and simultaneously increase its strength which results in higher axial deformation upon failure. Rise in gas pressure would increase the permeability and axial strain of raw coal on the whole and reduce its peak strength. Permeability first decreased and then increased during the loading of deviator stress, following a “V-shaped” change pattern. The results of sensitivity analysis indicated that confining pressure more significantly affected the peak strength and elastic modulus than gas pressure, while the gas pressure more significantly affected the permeability of the material than its confining pressure.